PLCG2 expression is associated with plaque‐associated microglia in Alzheimer's disease. (December 2021) - Tsai, Andy Po‐Yi; Dong, Chuanpeng; Moutinho, Miguel; Lin, Peter Bor‐Chian; Casali, Brad T; Bissel, Stephanie J; Oblak, Adrian L; Liu, Yunlong; Landreth, Gary E; Lamb, Bruce T.; Nho, Kwangsik
Abstract: Background: Alzheimer's disease (AD) is characterized by robust microgliosis and phenotypic changes that accompany disease pathogenesis. Genetic variants in microglial genes are associated with late‐onset AD (LOAD) risk. Phospholipase C𝛾2 (PLCG2) is selectively expressed by microglia in the brain and participates in the transduction of signals emanating from immune cell‐surface receptors that regulate the inflammatory response. Accumulating evidence from genetic association studies indicates the importance of PLCG2 in AD pathophysiology. However, the role of PLCG2 in AD is still poorly understood. Method: Using whole genome sequencing (N=1, 894) and RNA‐Seq (N=1, 077) data from the AMP‐AD cohort, we observed significant up‐regulation of PLCG2 in the parahippocampal gyrus, superior temporal gyrus, and inferior temporal gyrus in LOAD patients that positively correlated with amyloid plaque density. Gene expression analysis and expression quantitative trait loci (eQTL) of PLCG2 were conducted. We also evaluated the relationship between PLCG2 expression levels and amyloid plaque density and expression levels of microglia specific markers ( AIF1 and TMEM119 ). Age, sex, and APOE ε4 carrier status were used as covariates. Finally, we investigated the longitudinal changes PLCG2 expression in the 5XFAD mouse model of AD and it relationship to amyloid pathology progression. Importantly, increased Plcg2 expression levels in 5xFAD mice were limited to plaque‐associated microglia and were abolished entirely by eradicating microglia. Furthermore, eQTL analysis identified several variants associated with increased PLCG2 expression levels in the brain and other organs. Result: Using RNA‐Seq (N=1, 077) data from the Accelerating Medicines Partnership‐Alzheimer's Disease (AMP‐AD) cohort, we observed significant up‐regulation of PLCG2 in the parahippocampal gyrus, superior temporal gyrus, and inferior temporal gyrus in LOAD patients that positively correlated with amyloid plaque density. These findings were validated in the 5xFAD amyloid mouse model, which demonstrated disease progression‐dependent increases in Plcg2 expression that were associated with amyloid pathology. Importantly, increased Plcg2 expression levels in 5xFAD mice were limited to plaque‐associated microglia and were abolished entirely by eradicating microglia. Furthermore, eQTL analysis identified several variants associated with increased PLCG2 expression levels in the brain and other organs. Conclusion: Together, our findings provide further evidence that PLCG2 plays an important role in AD pathophysiology and is a potential target for microglia‐targeted AD therapies.